IN VITRO STUDY OF DISCOLORATION OF ORTHODONTIC CLEAR ELASTIC LIGATURE - Mioara Decusară; Daniela Cornea; Gabriela-Violeta Iordăchiță; Ada Ștefănescu (Romanian Society of Oral Rehabilitation, 2022)
Aim of the study: The aim of this paper is to evaluate the color changes of orthodontic clear elastic ligature after soaking three days in dietary and medical medium. Material and methods: For the study were used modules of transparent elastic ligatures from four orthodontic brands: AO (American Orthodontics, USA), GAC (Dentsply-GAC, USA), O.T (Ortho Technology, USA), DB (DB-Orthodontics UK). These were soaked in 250 ml glasses with the following liquid medium: artificial saliva (control), fruit juice, coffee, red wine, solution with methylene blue (existing in tablets for oral-pharyngeal disinfection) and solution with revelator of bacterial plaque(pink). The glasses with solutions were kept for 72 hours in a 37 degree in an incubator and the pigmentation of the clear elastic ligature were photographed at an interval of 24, 48 and 72 hours, forty students observing differences in discoloration between the various types of orthodontic clear elastic ligatures. Analysis involved the use of scores according to the degree of staining, in which: 0 = nonpigmented ligatures; 1 = slightly pigmented; 2 = moderately pigmented; and 3 = heavily pigmented. Results: There were signiﬁcant differences in discolouration depending on the type of elastomeric modules, immersion solution, and immersion period .